2018
DOI: 10.1007/s40732-018-0268-1
|View full text |Cite
|
Sign up to set email alerts
|

Pair Housing Alters Delay Discounting in Lewis and Fischer 344 Rats

Abstract: Impulsive choice underlies several psychological disorders and can be assessed in laboratory rats using delay-discounting tasks, in which choice is for either one food pellet immediately or three food pellets after a delay. Choice for the smaller, immediate reinforcer is considered the impulsive choice. Lewis (LEW) and Fischer 344 (F344) rats differ in the number of impulsive choices made during this task when singly housed, with LEW choosing the impulsive option more often. Due to increasing recommendations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These findings are consistent with literature investigating the between‐subjects effects of economic context on delay discounting (Green et al, 1996), suggesting that lower economic context decreases tolerance for delays to reward receipt. Nonhuman animal research investigating the effects of environmental enrichment has also predominantly found that rats reared in enriched contexts display less impulsive choice than their counterparts reared in impoverished environmental contexts (Bardo et al, 2001; Perry et al, 2008; Turturici et al, 2018; Yates et al, 2019). Similarly, these findings are consistent with findings using real‐world data to demonstrate that higher inflation increases within‐subject delay discounting (Ostaszewski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with literature investigating the between‐subjects effects of economic context on delay discounting (Green et al, 1996), suggesting that lower economic context decreases tolerance for delays to reward receipt. Nonhuman animal research investigating the effects of environmental enrichment has also predominantly found that rats reared in enriched contexts display less impulsive choice than their counterparts reared in impoverished environmental contexts (Bardo et al, 2001; Perry et al, 2008; Turturici et al, 2018; Yates et al, 2019). Similarly, these findings are consistent with findings using real‐world data to demonstrate that higher inflation increases within‐subject delay discounting (Ostaszewski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“… 15 17 ; although these effects may be moderated by genotype e.g. 18 , 19 . Moreover, EE has been shown to exert beneficial effects in animal models of a wide variety of neurodegenerative and neuropsychiatric disorders 20 , 21 , including disorders associated with behavioral dysregulation such as ADHD, autism, schizophrenia, and substance abuse disorder e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the probability values used during these procedures are usually 100, 75, 50, 25, and PROBABILITY DISCOUNTING OF LEWIS AND FISCHER 344 RATS 37 12.5%, which creates a situation where optimal choice is for the larger, uncertain reinforcer during the 100% and 75% probability blocks, 50% serves as an optimal switchover point, and optimal choice is for the smaller, certain reinforcer during the 25% and 12.5% probability blocks. However, in an attempt to match choice alternatives to those used during delaydiscounting procedures with LEW and F344 (e.g., Anderson & Diller, 2010;Turturici et al, 2018), choice between one and three food pellets was used during the current study. Given that a one-versus-three-pellet procedure was used, probability values were adjusted to account for changes in larger-reinforcer magnitude and were 100, 66.7, 33.3, 16.7, and 8.3%.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%